Periodontitis is an inflammatory disease of oxidative stress: We should treat it that way. Issue 1 (25th August 2020) - Sczepanik, Fábio Sá Carneiro; Grossi, Márcio Lima; Casati, Márcio; Goldberg, Michael; Glogauer, Michael; Fine, Noah; Tenenbaum, Howard C.
Abstract: Periodontitis is a highly prevalent disease. As it progresses, it causes serious morbidity in the form of periodontal abscesses and tooth loss and, in the latter stages, pain. It is also now known that periodontitis is strongly associated with several nonoral diseases. Thus, patients with periodontitis are at greater risk for the development and/or exacerbation of diabetes, chronic obstructive pulmonary disease, and cardiovascular diseases, among other conditions. Although it is without question that specific groups of oral bacteria which populate dental plaque play a causative role in the development of periodontitis, it is now thought that once this disease has been triggered, other factors play an equal, and possibly more important, role in its progression, particularly in severe cases or in cases that prove difficult to treat. In this regard, we allude to the host response, specifically the notion that the host, once infected with oral periodontal pathogenic bacteria, will mount a defense response mediated largely through the innate immune system. The most abundant cell type of the innate immune system – polymorphonuclear neutrophils – can, when protecting the host from microbial invasion, mount a response that includes upregulation of proinflammatory cytokines, matrix metalloproteinases, and reactive oxygen species, all of which then contribute to the tissue damage and loss of teeth commonly associated with periodontitis. Of the mechanisms referred to here, we suggest that upregulation of reactive oxygen species might play one of the most important roles in the establishment and progression of periodontitis (as well as in other diseases of inflammation) through the development of oxidative stress. In this overview, we discuss both innate and epigenetic factors (eg, diabetes, smoking) that lead to the development of oxidative stress. This oxidative stress then provides an environment conducive to the destructive processes observed in periodontitis. Therefore, we shall describe some of the fundamental characteristics of oxidative stress and its effects on the periodontium, discuss the diseases and other factors that cause oxidative stress, and, finally, review potentially novel therapeutic approaches for the management (and possibly even the reversal) of periodontitis, which rely on the use of therapies, such as resveratrol and other antioxidants, that provide increased antioxidant activity in the host.